Biophysical Modeling of Water Economy Can Explain Geographic Gradient of Body Size in Anurans - Gouveia, Sidney F.; Bovo, Rafael P.; Rubalcaba, Juan G.; Da Silva, Fernando Rodrigues; Maciel, Natan M.; Andrade, Denis V. [UNESP]; Martinez, Pablo Ariel (Univ Chicago Press, 2019)
Geographical gradients of body size express climate-driven constraints on animals, but whether they exist and what causes them in ectotherms remains contentious. For amphibians, the water conservation hypothesis posits that larger bodies reduce evaporative water loss (EWL) along dehydrating gradients. To address this hypothesis mechanistically, we build on well-established biophysical equations of water exchange in anurans to propose a state-transition model that predicts an increase of either body size or resistance to EWL as alternative specialization along dehydrating gradients. The model predicts that species whose water economy is more sensitive to variation in body size than to variation in resistance to EWL should increase in size in response to increasing potential evapotranspiration (PET). To evaluate the model predictions, we combine physiological measurements of resistance to EWL with geographic data of body size for four different anuran species. Only one species, Dendropsophus minutus, was predicted to exhibit a positive body size-PET relationship. Results were as predicted for all cases, with one species-Boana faber-showing a negative relationship. Based on an empirically verified mathematical model, we show that clines of body size among anurans depend on the current values of those traits and emerge as an advantage for water conservation. Our model offers a mechanistic and compelling explanation for the cause and variation of gradients of body size in anurans.
Keywords: allometry; biophysical model; ectotherms; evaporative water loss; macrophysiology; water conservation hypothesis